Development of Truth or Dare Card-Based Learning Media for Teaching Reaction Rates in Senior High School - Fanisah Ismi Hidayah‎; Fitriani‎; Hamdil‎ Mukhlishin (JPI: Jurnal Pustaka Indonesia, 2026)
Chemistry learning on reaction rate material often faces challenges due to its abstract and complex nature, which can hinder students’ conceptual understanding and reduce their engagement in the learning process. These challenges are compounded by the predominance of lecture-based instruction and the limited use of interactive learning media. This study aimed to develop a Truth or Dare card-based learning media for reaction rate material and evaluate its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) approach using a modified 4-D model consisting of three stages: define, design, and develop. The participants were 36 eleventh-grade students of SMAN 2 Sungai Raya, including 9 students in a small-scale trial and 27 students in a large-scale trial. Data were collected through observations, interviews, documentation, questionnaires, and tests. The instruments included material and media expert validation sheets, student response questionnaires, and pretest–posttest assessments. The results indicated that the Truth or Dare card media achieved a validity score of 96.66% from both material and media experts, categorized as very valid. The practicality scores reached 86.67% in the small-scale trial and 89.26% in the large-scale trial, indicating a very practical category. The effectiveness test showed N-gain scores of 0.84 and 0.91 in the small- and large-scale trials, respectively, both classified as high. These findings demonstrate that the developed media is valid, practical, and effective for enhancing student engagement and learning outcomes in reaction rate learning at the senior high school level.